Sosialisasi Pemanfaatan Hasil Pertanian Sebagai Produk Bisnis dari Petani Biasa Menjadi Petani Luar Biasa - Sriyani Mentari; Makaryanawati Makaryanawati; Dian Syariati (Asosiasi Dosen Akuntansi Indonesia, 2020)
Agriculture is a strategic land for economic development. This is supported by the fact that Indonesia had around 8 million hectares of paddy fields in 2017, which has not been added to the area of land, and land that is temporarily not being cultivated. With this area, of course, it can be calculated the amount of agricultural products obtained. But in reality, the level of poverty in Indonesia is still dominated by rural communities which incidentally are farmers. This also happened to the people in Desa Ngembal, Kecamatan Tutur, Kabupaten Pasuruan, where the economic development of the village had not been significant for the last ten years. The socialization carried out aims to provide knowledge to the people of Desa Ngembal in developing village potential that is still minimal in utilization. The socialization explained about how to turn agricultural products into business products that have a selling power so that they can support the welfare of the community. In this socialization it was also conveyed about the procedures for managing business finances, including marketing business products and digital-based marketing strategies that could reach more consumers so as to expand market share.